EFL Teachers' Job Satisfaction Profile - Widyantoro, Agus; Alsamiri, Yasir; Priyana, Joko; Putro, Nurhidayanto Pancoro Setyo (LPMPP Universitas Negeri Yogyakarta, 2024)
Teachers' job satisfaction has been studied for decades. However, there has been no study investigating the profile of Indonesian EFL teachers' job satisfaction. This study aimed to find out the profile of Indonesian EFL teachers' job satisfaction. A sample of 340 EFL secondary school teachers consisting of 272 females and 68 males, 299 teachers with the undergraduate degree and 41 teachers with the master's degree, 34 teachers with 1-5 years of teaching, 60 teachers with 6-10 years of teaching, 53 teachers with 11-20 years of teaching, and 38 teachers with more than 21 years of teaching were involved in this study. The instrument utilized in this study was an adaptation of the instrument developed by Spector (1994) comprising pay, promotion, supervision, fringe benefits, contingent rewards, operating conditions, coworkers, nature of work, and communication and distributed to the teachers via google forms due to the pandemic situation. The data were then analyzed using the confirmatory factor analysis. The findings revealed that four factors emerged in the teacher job satisfaction model, that is, salary, supervision, service condition, and . colleagues. The item loading factors in this model ranged from 0.28 to 0.80 and the acceptable fit indices were Ï‡2 = 88.82; df = 48; Ï‡2/df = 1.49; TLI = 0.93, RMSEA = 0.05; SRMR = 0.04.